Should routine risk reduction procedures for the prevention and control of pandemics become a standard in all oncological outpatient clinics?: the prospective COVID-19 cohort study: protect-CoV - Fey, Theres; Erickson, Nicole; Stahler, Arndt; Muenchhoff, Maximilian; Keppler, Oliver Till; Ruehlmann, Katharina; Krauss-Pfeiffer, Gabriele; Steinberg, Hannah; Graf, Alexander; Krebs, Stefan; Blum, Helmut; Khatamzas, Elham; et al. (Medical oncology, 2022)
Limited knowledge exists on the effectiveness of preventive preparedness plans for the care of outpatient cancer patients during epidemics or pandemics. To ensure adequate, timely and continuous clinical care for this highly vulnerable population, we propose the establishment of preventive standard safety protocols providing effective early phase identification of outbreaks at outpatient cancer facilities and communicating adapted standards of care. The prospective cohort study Protect-CoV conducted at the LMU Klinikum from mid-March to June 2020 investigated the effectiveness of a rapid, proactive and methodical response to protect patients and interrupt SARS-CoV-2 transmission chains during the first pandemic wave. The implemented measures reduced the risk of infection of individual cancer patients and ensured safe adjunctive infusion therapy in an outpatient setting during the early COVID-19 pandemic. In addition to the immediate implementation of standard hygiene procedures, our results underscore the importance of routine PCR testing for the identification of asymptomatic or pre-symptomatic COVID-19 cases and immediate tracing of positive cases and their contacts. While more prospective controlled studies are needed to confirm these results, our study illustrates the importance of including preventative testing and tracing measures in the standard risk reduction procedures at all out patient cancer centers.